THE USE OF QUARRY DUST FOR PARTIAL REPLACEMENT OF CEMENT IN CEMENT-SAND MORTAR (FUDMA JOURNAL OF SCIENCES, 2021)
This research was carried out to investigate the effect of partially replacing cement with quarry dust in cement-sand mortar. Tests including setting times, water absorption, compressive strength and density test were carried out on mortar with cement partially replaced with 0%, 5%, 10%, 15%, 20%, 25% and 30% quarry dust and presented. Experimental results show that replacement of quarry dust as partial replacement of cement in cement-sand mortar decrease the initial and final setting times of cement paste and increase the water absorption of the mortar. The partial replacement shows an improvement of compressive strength at 5% quarry dust content after which there is a decrease with increase in quarry dust content at all the ages. The increase in compressive strength at 5% indicates possible pozzalanic activity at that level. Thus quarry dust can be utilized as cement replacement material at 5% dust content. Above this it can be utilized as fine aggregate replacement for use in low-strength mortar applications
Keywords: Quarry dust, cement-sand mortar, cement partial replacement, setting times, water absorption, compressive strength, density